Efeect of AM fungi with additonal phosphate fertilazation on growth and nutrient uptake in Guizotia abyssinica (L.f) Cass.var, RCR-18 - Gabriel, KP; Lakshman, HC; Yeasmin, Tanzima (Journal of Bio-Science, 2016)
Context: Arbuscular-Mycorrhizal fungi colonization in roots of many plants promotes the increased nutrient uptake especially the phosphorus from phosphorus deficient soil. Objective: To compare the efficacy of different concentration of recommended dosages of super phosphate fertilizers with inoculation of AM fungi to evaluate growth, nutrients uptake on Niger plant (Guizotia abyssinica (L.f) Cass. var, RCR-18). Materials and Methods: The effect of two Arbuscular mycorrhizal fungi Scutellospora nigra and Glomus mosseae with 4 different dosage (25%, 50%, 75%, 100% ) of superphosphate (P2O5) was treated on growth yield and nutrient uptake in Niger plant (Guizotia abyssinica (L.f) Cass. var, RCR-18) was evaluated under greenhouse conditions. Pots were watered they were harvested once in 30 days intervals. For 90 days the following readings viz., plant height, root length, biomass, grains yield, percent root colonization, spore number macro-micro nutrients contents in shoots and roots were determined. Results: Scutellospora nigra with 50% RDSP/kg showed a significant increase in the plant growth biomass of shoot and root of Guizotia abyssinica (L.f) Cass. var, RCR-18. Percent root colonization, seed number and N, P, K and Zn, Mg uptake in shoot and root. Conclusion: Overall, our results clearly suggest that synergistic and additive mechanisms involved can enhances the plant growth, nutrient uptake and adaptation to unfavorable drought soil conditions. J. bio-sci. 22: 45-51, 2014